ETIKA BISNIS ISLAM DALAM MANAJEMEN BISNIS KULINER - Inayah Swasti Ratih; Zainur Ridho; Siti Aisyah (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Introduction: The purpose of this research is to explain how the application of Islamic business ethics in the management of culinary business. Culinary business is a business that is widely pursued by the community because it is easy and needed by the market, but there are still many business people who heed islamic business ethics in their business management. Whereas business ethics is an important element of business management itself. Then there needs to be guidelines for businesses to apply Islamic business ethics into the management of culinary business. Methods: This research uses qualitative research with literature study method. Results: Islamic business ethics principles will be able to help culinary business management more targeted and have clear values both in the world and in the hereafter. These principles are 1) Tauhid, 2) Worship, 3) Amanah, 4) Hikmah, 5) Adil, 6) Ihsan, 7) Please help, 8) Halalan Thayyiban and 9) Deliberation. Because binsis activities not only to gain profit but to carry out the commandments of Allah SWT. Conclusion and suggestion: The principle of Islamic business ethics must be done in every business activity because it will be able to increase the productivity of the business. This research is only theoretical,so there needs to be further research that is empirical.